Integral and inclusive education in the Brazilian reality: challenges to be faced in teacher training - Miguel, Jose Carlos [UNESP]; Araujo, Gustavo Cunha de (Univ Federal Norte Tocantins-ufnt, 2024)
The purpose of this article is to discuss problems that affect the Brazilian society and the contemporary education from an inclusive perspective, as well as to discuss possibilities for better addressing the determinants related to teacher training. This is a qualitative research on the subject, based on the descriptors inclusive education, integral education, educational inequality, educational policies and teacher training in the SciELO Database - Scientific Electronic Library Online - and in the BDTD - Brazilian Digital Library of Theses and Dissertations, we selected the texts that are closest to the ideas listed above to define the article. We then established that in addition to the specificity of the pedagogical treatment of students with disabilities, an inclusive education process in the Brazilian reality requires considering the cultural diversity and uniqueness of the students included by the granting of the vacancy previously denied, but without guarantee of permanence in a condition of effective learning, coexisting with several intervening factors that can cause any situations outside of a predicted standard to be treated as a deviation, as a problem of the student, and not a political-pedagogical challenge for the school.
Keywords: inclusion; integral education; education